Research Hot Spots and Trends on Melatonin From 2000 to 2019 - Meng, Yan; Tao, Zhengbo; Zhou, Siming; Da, Wacili; Tao, Lin (Frontiers in Endocrinology, 2021)
Research on melatonin remains one of the major hot spots in the field of disease treatment, but relevant data are numerous. The purpose of this study was to quantitatively and qualitatively analyse the progress of melatonin research through the method of bibliometrics and to predict hot spots and trends in melatonin research. This study retrieved all the studies on melatonin from 2000 to 2019 in the Web of Science and PubMed and analysed the publishing trends in the literature on a bibliometric online analysis platform and CiteSpace software. The research results were also visually analysed to summarize melatonin research hot spots through gCLUTO and pubMR. The study retrieved a total of 20,351 publications, of which the number of US publications ranked first, accounting for 21.46%, with the greatest impact (centrality = 0.31). The University of Texas Health Science Center at San Antonio and Harvard University had the highest average number of citations at 43.19 and 33.96, respectively. Journal of Pineal Research had the highest average number of citations in 2,993 journals. Professor Reiter made the largest contribution to this area. We further analysed 100 highly cited articles for clinical applications and ongoing related clinical drug trials based on the first hot spot. We systematically analysed melatonin for nearly 20 years while predicting the main research trends in the future, which may provide new directions and ideas for melatonin research. The structure and normal physiological functions of melatonin have been intensively studied in the past few years. And clinical application research and target of melatonin treatment for different diseases and target-based drug design will certainly become the focus of melatonin research.